TAACCCT Impact on Meaningful Employer Engagement. Issue 193 (28th December 2020) - Cosgrove, John; Cosgrove, Maggie
Abstract: This chapter discusses the employment engagement efforts of Missouri's twelve community colleges to improve program development, student recruitment, program assistance, student support, and employer hiring.